Nostra aetate and the Islamic perspective of inter-religious dialogue - Shehu, Fatmir Mehdi (IIUM Press, 2008)
This book addresses the concept of inter-religious dialogue promoted by Nostra Aeate (The Declaration on the Relation of the Church to non-Christian Religions, promulgated on October 28, 1965), and the Holy Qur’an, as the only means to change the attitude of Muslims and Christians from that of hostility to mutual respect and better, objective and unbiased understanding of one another’s way of belief. Amicable Islamic-Christian inter-religious dialogue is thus seen as the only hope against obstacles that make religious co-existence difficult, and for bringing peace and harmony to the Muslim and Christian communities in particular and humanity in general.